Influence of Advertisement Message on Fitbar Billboard Towards Brand Awareness and Its Implication to Brand Image - Yuliana Riana Pand; Wiliany Gui (Humaniora, 2016)
The assumption that snacks could cause problem in diet and bodyweight, makes this study interesting. Because this product, Fitbar, appears on the market as a healthy snack that is contrary to this assumption. This product is about to prove that there is a healthy and tasty snack as snacks. Marketing communications through advertising billboards with the media aims to reach the target market. Fitbar billboard ads convey the message content in the form of information about the attributes and benefits of products such as nutritional content and product slogans. This study uses path analysis techniques to determine the effect of variable X (advertisement message) to variable Y (brand awareness) and its implications on the variable Z (brand image). The results showed that the content of the message components such as message structure, message display, message format, and the source of the message have contributed in the formation of brand awareness, which further on has implications on brand image. Influence on brand awareness message content is equal to 0.609. The effect of variable X (message) and Y (brand awareness) to variable Z (brand image) amounted to 0,365. Therefore, the use of billboards media in conveying the message to the target market of Fitbar products is to build brand awareness and the implications for brand image.